The Effect of Walking Exercise on Body Mass Index among Overweight and Obese Employees at Nusa Cendana University - Marcellino Cevin Kurniawan; Dyah Gita Rambu Kareri; I Made Artawan; M. Biomed (Pubmedia Jurnal Pendidikan Olahraga, 2025)
Obesity is a condition characterized by an imbalance between energy intake and energy expenditure over an extended period. Obesity and overweight are generally caused by unhealthy lifestyles, high sugar and fat dietary patterns, and lack of physical activity. Insufficient exercise is directly associated with an increase in Body Mass Index (BMI), a condition commonly found among employees and lecturers within university environments. A preliminary survey conducted by the Health Promoting University (HPU) reported that 58.5% of respondents at Nusa Cendana University do not engage in regular exercise, while data from the 2018 Basic Health Research (Riskesdas) showed that 13.6% of Indonesians over the age of 18 are obese. One effective management strategy for overweight and obesity is walking exercise, which can increase basal metabolic rate through ATP combustion, lipogenesis, and muscle mass enhancement, leading to higher heat production and resulting in weight reduction. This study aimed to examine the effect of walking exercise on BMI among overweight and obese employees at Nusa Cendana University. A quasi-experimental method with a nonequivalent control group design was applied, involving 20 participants in the intervention group and 20 in the control group. The results showed a significant change in BMI in the intervention group (p = 0.034) based on a paired sample t-test. It is concluded that walking exercise has a significant effect on reducing BMI among overweight and obese employees at Nusa Cendana University.